Coarse to Fine Audio-Visual Size Correspondences Develop During Primary School Age - Cuturi, Luigi F.; Tonelli, Alessia; Cappagli, Giulia; Gori, Monica (Frontiers in Psychology, 2019)
Developmental studies have shown that children can associate visual size with non-visual and apparently unrelated stimuli, such as pure tone frequencies. Most research to date has focused on audio-visual size associations by showing that children can associate low pure tone frequencies with large objects, and high pure tone frequencies with small objects. Researchers relate these findings to coarser association, i.e. less precise associations for which binary categories of stimuli are used such as in the case of low versus high frequencies and large versus small visual stimuli. This study investigates how finer, more precise, crossmodal audio-visual associations develop during primary school age (from 6 to 11 years old). To unveil such patterns, we took advantage of a range of auditory pure tones and tested how primary school children match sounds with visually presented shapes. We tested 66 children (6-11 y.o.) in an audio-visual matching task involving a range of pure tone frequencies. Visual stimuli were circles or angles of different sizes. We asked participants to indicate the shape matching the sound. All children associated large objects/angles with low pitch, and small objects/angles with high pitch sounds. Interestingly, older children made greater use of intermediate visual sizes to provide their responses. Indeed, audio-visual associations for finer differences between stimulus features such as size and pure tone frequencies, may develop later depending on the maturation of supramodal size perception processes. Considering our results, we suggest that audio-visual size correspondences can be used for educational purposes by aiding the discrimination of sizes, including angles of different aperture. Moreover, their use should be shaped according to children’s specific developmental stage.